2006
DOI: 10.1093/ps/85.2.344
|View full text |Cite
|
Sign up to set email alerts
|

Stocking Density Effects on Male Broilers Grown to 1.8 Kilograms of Body Weight

Abstract: This study examined the effects of stocking density on live performance, physiological stress level indicators, and processing yields of male broilers grown to 1.8 kg. A total of 3,120 Ross x Ross 708 male chicks was placed into 32 floor pens (5.57 m2/pen). Stocking density treatments were 25, (75 birds/pen), 30 (90 birds/ pen), 35 (105 birds/pen), and 40 (120 birds/pen) kg of BW/m2. The BW gain, feed consumption, and feed conversion were adversely affected with increasing stocking densities by 35 d. Physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

36
109
3
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(157 citation statements)
references
References 23 publications
36
109
3
9
Order By: Relevance
“…When examined carcass characteristics (Table 2), stocking density did not affect the carcass yield and other carcass features as also reported by previous studies (Feddes et al 2002;Dozier et al 2006). However, ad libitum feeding program increased breast meat ratio parallel to increasing BW and reduced wings, neck and back ratios.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…When examined carcass characteristics (Table 2), stocking density did not affect the carcass yield and other carcass features as also reported by previous studies (Feddes et al 2002;Dozier et al 2006). However, ad libitum feeding program increased breast meat ratio parallel to increasing BW and reduced wings, neck and back ratios.…”
Section: Resultssupporting
confidence: 81%
“…Any deviation from optimal conditions may impair performance (Imaeda 2000;Dozier et al 2006). High stocking density can reduce performance because of several factors such as high environmental temperature in the microclimate of the bird, inadequate air exchange, increasing ammonia level and impeded access to feed and water (Thomas et al 2004;Muniz et al 2006;Onbasilar et al 2008).…”
mentioning
confidence: 99%
“…Similar results were reported by Dozier et al (2005a) and Onbasilar (2008), who observed FCR improvement as housing density increased in young broilers. It should be noted that, despite of the lack of statistical significance (p≥0.05), the best FCR and the lowest FI at the lowest density were obtained only during the period of 21-28 days of age.…”
Section: Resultssupporting
confidence: 90%
“…Rearing density had no effect on weight gain. Moreira et al (2004) obtained higher DWG in broilers housed at higher densities, but other studies reported no effect (Ravindran et al, 2006) or negative effects (Dozier et al, 2005a) on increasing rearing densities.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation